2000
DOI: 10.1002/(sici)1098-2396(200004)36:1<21::aid-syn3>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Dual control of dorsal raphe serotonergic neurons by GABAB receptors. Electrophysiological and microdialysis studies

Abstract: We assessed the role of GABA(B) receptors in the control of serotonergic (5-HT) neurons of the dorsal raphe nucleus (DRN) by using microdialysis in vivo and intra- and extracellular recording in vitro in the rat. The GABA(B) agonist R(+)baclofen (but not the inactive S(-)enantiomer) enhanced the 5-HT output in the DRN (4. 7-fold at 15 mg/kg s.c.) and, to a much lesser extent, striatum of unanesthetized rats. Phaclofen (2 mg/kg s.c.) antagonized the effects of 6 mg/kg R(+)baclofen in dorsal striatum. Using dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…These data perhaps suggest that EMS causes an increase in the spontaneous in vivo activity of a sub-population of classical (nonbursting) DRN 5-HT neurons. Increased ®ring rate would be consistent with increased a 1adrenoceptor-mediated excitation or decreased 5-HT 1A receptor inhibition and/or changes in tonic regulation of these neurons by other neurotransmitters (Baraban & Aghajanian, 1980;Pin Äeyro & Blier, 1999;Abellan et al, 2000). However, in spite of any possible increased activity of a proportion of 5-HT neurons, it is of note that in our in vivo microdialysis study we found no increase in basal 5-HT levels in the frontal cortex.…”
Section: Discussionsupporting
confidence: 52%
“…These data perhaps suggest that EMS causes an increase in the spontaneous in vivo activity of a sub-population of classical (nonbursting) DRN 5-HT neurons. Increased ®ring rate would be consistent with increased a 1adrenoceptor-mediated excitation or decreased 5-HT 1A receptor inhibition and/or changes in tonic regulation of these neurons by other neurotransmitters (Baraban & Aghajanian, 1980;Pin Äeyro & Blier, 1999;Abellan et al, 2000). However, in spite of any possible increased activity of a proportion of 5-HT neurons, it is of note that in our in vivo microdialysis study we found no increase in basal 5-HT levels in the frontal cortex.…”
Section: Discussionsupporting
confidence: 52%
“…In accordance with that, microdialysis studies have shown that under lights-off conditions the infusion of the GABA B agonist baclofen in the DR diminishes the release of 5-HT (Tao et al 1996). However, during the lights-on period baclofen infusion in the DR and MnR increases 5-HT release, indicating a disinhibitory action (Abellán et al 2000b). This view is also supported by intracellular recordings of dorsal raphe nucleus (DR) 5-HT neurones in midbrain slices, showing that baclofen at low concentrations (IC 50 ¼ 72 nM) counteracts GABA A -mediated inhibitory post-synaptic currents in 5-HT neurones, whereas higher concentrations (IC 50 ¼ 1.4 lM) are required to elicit a direct inhibitory effect (Abellán et al 2000b).…”
supporting
confidence: 56%
“…This observation together with the present data showing the occurrence of GABA B receptor mRNA in both or 5-HTT mRNA-positive and GAD-containing cells in the raphe nuclei provides anatomical support to the hypothesis expressed by Abellán et al (2000b) to explain the dual effect of the GABA B agonist baclofen on 5-HT cells. Thus, post-synaptic GABA B receptors located on serotonergic neurones could mediate the inhibition of 5-HT release caused by baclofen (Tao et al 1996), whereas the activation of pre-synaptic GABA B receptors located in GABAergic cells would result in a final disinhibitory action on serotonergic neurones (Abellán et al 2000a(Abellán et al , 2000b. It should be pointed out that, according to our observations, GAD/ GABA B receptor mRNA-containing cells in the raphe nuclei are not abundant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), a g-aminobutyric acid B (GABA) agonist, which also, did not restore the number of spontaneously ®ring neurons suggesting that the silent neurons were not depolarized. However, a lack of repolarizing eect of the GABA B agonist could not be totally excluded based on recent ®ndings suggesting that, under some circumstances, (+)baclofen might disinhibit DRN 5-HT neurons by preferentially activating GABA B autoreceptors (Abellan et al, 2000). Therefore, at present the possibility of a depolarization blockade cannot be completely ruled out and we will be further investigating this phenomenon as this would be the ®rst report of such a phenomenon occurring in 5-HT neurons.…”
Section: Figurementioning
confidence: 92%